1987
DOI: 10.1021/bi00375a005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid mobility and order in bovine rod outer segment disk membranes. A spin-label study of lipid-protein interactions

Abstract: Lipid-protein interactions in bovine rod outer segment disk membranes have been studied by using a series of eight stearic acid spin-label probes which were labeled at different carbon atom positions in the chain. In randomly oriented membrane dispersions, the electron spin resonance (ESR) spectra of the C-8, C-9, C-10, C-11, C-12, C-13, and C-14 atom positional isomers all apparently consist of two components. One of the components corresponds closely to the spectra obtained from dispersions of the extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 40 publications
6
40
0
Order By: Relevance
“…4 (19,20), in qualitative agreement with the present results. In contrast, fluorescent-probe measurements on the other systems have been interpreted to suggest that an increase in order of the lipid chains is induced by the protein (21,22), contrary to the present direct measurements.…”
supporting
confidence: 92%
“…4 (19,20), in qualitative agreement with the present results. In contrast, fluorescent-probe measurements on the other systems have been interpreted to suggest that an increase in order of the lipid chains is induced by the protein (21,22), contrary to the present direct measurements.…”
supporting
confidence: 92%
“…Information about chain orientation and ordering can be obtained from ESR measurements with macroscopically aligned samples [12]. This has been done for oriented rod outer segment discs: it was found that there is a wide orientational distribution, i. e. a considerable degree of disorder, of the lipid chain segments associated with the visual receptor rhodopsin [13].…”
Section: Spin-label Esrmentioning
confidence: 99%
“…A variety of electron paramagnetic resonance (EPR) parameters are available to characterize the environmental polarity. These include hyperfine couplings in conventional EPR (3)(4)(5), g-values in high-field EPR (6), relaxation enhancement by molecular oxygen (7)(8)(9), and direct detection of penetrant water by pulsed EPR (10,11).…”
Section: Introductionmentioning
confidence: 99%